(untitled) (Bangladesh Journal of Pharmacology, 2016)
The marine sponge Neopetrosia contains about 27 species that is highly distributed in Indian Ocean, Atlantic Ocean (Caribbean Sea) and Pacific Ocean. It has proven to be valuable to the discovery of medicinal products due to the presence of various types of compounds with variable bioactivities. More than 85 compounds including alkaloids, quinones, sterols and terpenoids were isolated from this genus. Moreover, the crude extracts and the isolated compounds revealed activities such as antimicrobial, anti-fouling, anti-HIV, cytotoxic, antitumor, antioxidant, anti-protozoal, anti-inflammatory. Because only 9 out of 27 species of the genus Neopetrosia have been chemically studied thus far, there are signiﬁcant opportunities to ﬁnd out new chemical constituents from this genus.